ANALISIS ASUHAN KEPERAWATAN KELUARGA DENGAN INTERVENSI OLAHRAGA JALAN KAKI UNTUK MENGURANGI IMT DAN PERILAKU SENDENTARY PADA ANAK DENGAN OBESITAS DI KELURAHAN GROGOL KECAMATAN LIMO KOTA DEPOK - Della Yunita (2023)
Overweight and obesity is a problem of excess nutrition that is increasingly common in children around the world. Overweight and obesity in children is the result of calorie (energy) intake that exceeds the number of calories expended or burned through metabolic processes in the body. Lifestyle changes that lead to westernization and sedentary life styles are often found in big cities in Indonesia. Simple physical activities that can overcome obesity in children include walking. Walking is a way to increase physical activity that is simple, easy, and can be done by anyone at any time. This writing aims to determine the effectiveness of walking interventions for reducing body mass index in school-age children. This intervention is carried out 3 times in 1 week in managed and resume patients who have obesity problems. The intervention was carried out at RT 03 RW 09, Grogol, Limo, Depok. The resulut of the 4 weeks of implementation, it was found that there was a decrease in weight in the treated patients by 2 kg with a decrease in BMI of 0.85 SD. In resume patients, there was a weight loss of 1 kg with a decrease in BMI of 0.4 SD. So it can be concluded that the walking intervention had an effect on reducing body mass index in school-age children. Community nurses are expected to be able to apply walking as a management method for overcoming weight and obesity in school-age children.